Pencegahan dan Penyebaran Wabah Covid-19 di Daerah Pesisir - Widiastuti, Linda; Liestyaningrum, Wiwiek; Wati, Liza; Rahardiantini, Ikha; Siagian, Yusnaini; Atrie, Utari Yunie (Universitas Baiturrahim, 2024)
COVID-19 is an acute respiratory disease caused by a new type of corona virus. This disease first broke out in Wuhan, China and then spread to almost the entire world and caused a global pandemic. Main symptoms. Covid-19 includes cough, fever and shortness of breath. This disease attacks all age groups: adults, the elderly, and children. Coastal communities need to get easy-to-understand education about Covid-19 and ways to prevent it. This is the basis for the community service team for the professional study program Ners Stikes Hang Tuah Tanjungpinang to actively participate in efforts to prevent and control the Covid-19 virus by providing counseling or outreach about Covid-19 and its prevention efforts to coastal communities on the Nyirih River. The results obtained were 115 people with elementary education background 86 people (75.6%), infected with Covid-19 10 people (8.6%) positive antigen, cormobid hypertension 28 people (24.3%), cormobid DM 12 people (10 .4%) who have hyperglycemia blood glucose levels. The majority of participants have high risk factors for being infected with Covid-19 which can cause respiratory failure and death in the Comorbid group